Review on 2D Arsenene and Antimonene: Emerging Materials for Energy, Electronic and Biological Applications. Issue 23 (11th July 2022) - Dongre S, Sumanth; R, Shwetharani; Hunsur Ravikumar, Chandan; C, Lavanya; Balakrishna, R. Geetha
Abstract: Monoelemental 2D materials such as arsenene (As) and antimonene (Sb) are creating great interest in materials research (since 2014) for designing various optoelectronic devices, energy production, and storage systems such as sensors, electrically modifiable displays, transistors, and catalysts owing to their unique properties like high surface area, optical, electrical, mechanical properties, and bio‐compatibility. Here in, an attempt has been made to write a comprehensive review on recent progress of monoelemental arsenene and antimonene focusing on tuning of properties through various techniques and their potential applications in different fields. The review is designed to explain the fundamental structures and properties in the beginning, followed by different preparation methods like exfoliation, ball milling, molecular beam epitaxy, chemical vapor deposition, and plasma‐assisted synthesis. Furthermore, the details on density functional theory studies of As an Sb and their applications in various fields such as photocatalysis, electronic and optoelectronic fields, solar cells, hydrogen evolution reaction, supercapacitors, batteries, biological applications, sensing, and electrochemical devices are reported. Abstract : This review discusses the properties, synthesis processes, and application of 2D monoelemental arsenene and antimonene in recent years. The main aim of the review is to study and encourage the research on arsenene and antimonene so that they can be applied in energy, electronic, and biological applications which further helps in betterment of society.